2022
DOI: 10.3390/jcm11113168
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Deep-Learning-Based Ultra-Wide-Field Fundus Imaging and True-Colour Confocal Scanning for Diagnosing Glaucoma

Abstract: In this retrospective, comparative study, we evaluated and compared the performance of two confocal imaging modalities in detecting glaucoma based on a deep learning (DL) classifier: ultra-wide-field (UWF) fundus imaging and true-colour confocal scanning. A total of 777 eyes, including 273 normal control eyes and 504 glaucomatous eyes, were tested. A convolutional neural network was used for each true-colour confocal scan (Eidon AF™, CenterVue, Padova, Italy) and UWF fundus image (Optomap™, Optos PLC, Dunferml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Transfer learning is a DL method in which a model trained for one task is repurposed for a related second task. We utilized the weight of the backbone network by applying this fine-tuning of the transfer learning method with SS-OCT images [24,25] using ResNet18 pre-trained with ImageNet (Figure S1). For pre-training, the SS-OCT RNFL thickness map (12 × 9 mm) of glaucoma and normal groups was used (Figure 1).…”
Section: Techniques: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer learning is a DL method in which a model trained for one task is repurposed for a related second task. We utilized the weight of the backbone network by applying this fine-tuning of the transfer learning method with SS-OCT images [24,25] using ResNet18 pre-trained with ImageNet (Figure S1). For pre-training, the SS-OCT RNFL thickness map (12 × 9 mm) of glaucoma and normal groups was used (Figure 1).…”
Section: Techniques: Proposed Methodsmentioning
confidence: 99%
“…All participants underwent WF-OCTA imaging with the same SS-OCT device (Topcon, DRI OCT Triton), and the glaucoma was diagnosed by a glaucoma specialist. Diagnosis of glaucoma and selection of the control group were performed similarly to that in previous studies (Supplementary Materials) [24,25]. To eliminate ambiguity, this study excluded patients with high myopia (sph < −6.0D), retinal diseases, and glaucoma suspect states without definite visual field impairment or RNFL defects.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Few studies have been published regarding AI algorithms for glaucoma detection from widefield fundus photos. Shin et al 31 compared CNN-based algorithms using ultrawide-field (UWF) fundus images versus true-color confocal scans for the diagnosis of glaucoma. In this study, the DL algorithm based on UWF imaging achieved a higher accuracy and AUC (ACC 83.62%, AUC 0.904 vs. ACC 81.46%, AUC 0.868).…”
Section: Widefield Fundus Photo Algorithmsmentioning
confidence: 99%
“…It can be used for automated central fundus lesion detection, even in external datasets (collected by different types of cameras) from subjects with various ethnic backgrounds in two countries. In 2022, Shin et al [36] evaluated and compared the performance of UWF imaging and truecolor confocal scanning images in detecting glaucoma based on the DL classifier. They found that the ability of DL-based UWF imaging and true-color confocal scanning to diagnose glaucoma was comparable to that of the OCT parameter-based method.…”
Section: Introductionmentioning
confidence: 99%